EFEITO DO TREINAMENTO AERÓBIO NOS PARÂMETROS CARDIOVASCULARES DE PACIENTES EM HEMODIÁLISE - AZOUBEL, Luana Manaisse (2017)
Introduction: Chronic kidney disease is an epidemical problem raising all over the world, it is estimated that one million individuals undergo dialysis treatment and in Brazil this number is around 112.000. Several studies have been shown the high prevalence of autonomic disfunction in hemodialysis patients and this disfunction is associated to cardiac events such sudden cardiac death, heart failure and myocardial infarction. In contrast, aerobic training is an important ally in autonomic improvement and hence in heart rate variability. Objective: Verify cardiovascular adaptations 12 weeks post aerobic training in hemodialysis patients. Materials and methods: 14 patients undergoing hemodialysis treatment joined the study, they were divided in two groups, a control group (GC) and active group (GA), both with 7 subjects (4 women). This study occurred at Centro de Prevenção de Doenças Renais at Hospital Universitário Presidente Dutra of Universidade Federal do Maranhão and Centro de Nefrologia do Maranhão. The subjects of GA underwent an aerobic exercise protocol, an intensity between 60% and 80% of maximal heart rate. The data normality was analyzed by Shapiro-Wilk test, for groups characterization we adopted Student’s paired T test and Wilcoxon for non parametrics values. Statistical analysis between groups was tested with two-way ANOVA and post-hoc Student Newman-Keulls. Results: Body composition between groups was different for both body mass index from 24,71±2,34 to 18,88±1,83 and fat mass 22,70±4,94 to 13,69±3,05 in GA. Cardiovascular parameters in GA, resting heart rate was lower in post training 77,14±9,08 to 69,86±7,53 and VO2 values rised significantly from 18,98±0,82 to 22,53±2,63 in comparision between baseline and after 12 weeks the values. Systolic blood pressure was lower at sleep period, with 120,80±10,85 (mmHg) in baseline and 109,00±15,00 (mmHg) post training at Day 1 and also in Day 2, with 127,20±15,82 mmHg in baseline and 110,70±16,40 mmHg post training. In Day 2, after aerobic protocol intervention there was a reduction in systolic blood pressure value from waking period to sleep period, with 125,50±17,03 mmHg and 110,70±16,40 mmHg respectively. In regard to GA autonomic modulation, HF (n.u) index improved from 47,41±15,95 (n.u) to 69,35±19,3 (n.u) and sympathovagal balance decreased from 1,20±0,60 to 0,59±0,68, when compared their baselines and after 12 weeks values. Between groups, GA showed better values, HF (n.u) index and LF/HF respectively were 69,35±19,37 (n.u); 0,59±0,63 and 43,63±21,07 (n.u); 2,40±3,13 and GC the values were 43,63±21,07 (n.u); and 2,40±3,13. Conclusion: Moderate aerobic training, in 12 weeks, improved cardiorespiratory fitness and autonomic modulation in hemodialysis patients. Besides, GA at the end of this study had better body composition values then GC.